Analysis of Types of Flexible Pavement Damage Using the Pavement Condition Index Method - Novianto, Dicky; Rulhendri; Chayati, Nurul (Journal of Applied Civil Engineering and Infrastructure Technology, 2024)
Roads are land transportation infrastructure that is very important in facilitating economic relations and other social activities. If road damage occurs, it will not only result in the obstruction of other economic and social activities but can also cause accidents for road users. The aim of this research is to explain the types of damage to the surface layer of flexible pavement and to find out the index value of the pavement condition index for Jalan Kreteg-Lebak Jaya based on the PCI (Pavement Condition Index) method so that the results can be used in preparing road maintenance programs. The results of this research in segment 1 showed 4 types of damage, namely edge cracks, patches, holes, weathering, and loose granules, with a PCI value of 22, very poor pavement conditions using this type of treatment. reconstruction/recycling. In segment 2, there were 4 types of damage, namely edge cracks, patches, holes, weathering, and loose granules with a PCI value of 26 in poor pavement conditions using the type of reconstruction or recycling treatment. In segment 3, there were 3 types of damage: holes, slip cracks, weathering, and loose granules with a PCI value of 46. Fair pavement conditions using reconstruction or recycling treatment in segment 4, there were 4 types of damage, namely crocodile skin cracks, edge cracks, holes, weathering, and loose granules, with a PCI value of 29 for poor pavement conditions using the type of reconstruction or recycling treatment.